Call to honour in service of emergent India - Singh, Jaswant 1938-2020. (New Delhi Rupa & Co., 2006)
India's foreign relations during the period 1998-2004; first hand account by former foreign minister of India.
Includes index.
Keywords: Singh, Jaswant, -- 1938-2020.; India -- Foreign relations -- 1984-; India -- Politics and government -- 1977-